PENGARUH BUDAYA ORGANISASI DAN KOMITMEN ORGANISASI TERHADAP LOYALITAS ANGGOTA BUMDES DI DESA KUKUH WINANGUN - Gusti Ayu Made Rina Widiyaniti; I Gusti Ayu Wimba; I Gede Aryana Mahayasa (Universitas Triatma Mulya, 2021)
BUMDes is a vehicle for running businesses in the village, the problem that occurs in BUMDes in Kukuh Winangun Village is that the lack of member loyalty is caused by other choices that they think are better than BUMDes. The formulation of the problem and the purpose of this research is to determine the effect of organizational culture and organizational commitment on member loyalty. This research was conducted at BUMDes, Kukuh Village, Marga District, Tabanan Regency. The population in this study was the total number of BUMDes members in Kukuh Winangun Village, Marga District, Tabanan Regency, which amounted to 1,166 members consisting of 8 official banjars, 12 traditional villages, then a sample of 93 respondents was determined. The data analysis technique used is validity test, reliability test, classical assumption test, multiple linear regression analysis test, determination, partial (t) and simultaneous (f) significant test. Based on the results of the analysis, it was found that partially organizational culture (X1) has a positive and significant effect on member loyalty (Y). Partial organizational commitment (X2) has a positive and significant effect on member loyalty (Y). There is a simultaneous influence of organizational culture and organizational commitment variables on member loyalty. Suggestions that can be given to BUMDes in Kukuh Winangun Village are to improve and strengthen communication patterns between village institutions by holding regular monthly or quarterly meetings to discuss the development of BUMDes so that the development of BUMDes can be known by all parties in Kukuh Winangun Village.